Interictal behaviour in hospitalised temporal lobe epileptics: relationship to idiopathic psychiatric syndromes. Issue 6 (June 1982) - Bear, D; Levin, K; Blumer, D; Chetham, D; Ryder, J
Abstract : Temporal lobe epileptics undergoing psychiatric hospitalisation were contrasted with patients suffering idiopathic psychiatric syndromes or other epilepsies. Quantitative ratings from blind interviews conducted according to a protocol confirmed the appearance of a statistically distinctive behavioural profile, including the desire for social affiliation, circumstantiality, religious and philosophic interests, and deepened affects, among the temporal lobe epileptics.